Dural venous sinus thrombosis: The combination of noncontrast CT, MRI and PC-MR venography to enhance accuracy - Ozturk, Kerem (Neuroradiol J, 2018)
AIM: The aim of this article is to determine whether a combination of noncontrast CT (NCCT), three-dimensional-phase contrast magnetic resonance venography (3D PC-MRV), T1- and T2-weighted MRI sequences can help to identify acute and subacute dural venous sinus thrombosis (DVST) with greater accuracy. METHODS: A total of 147 patients with DVST (n = 30) and a control group (n = 117) underwent NCCT, T1- and T2-weighted MRI sequences, and 3D PC-MRV from 2012 to 2016. Two experienced observers interpreted the images retrospectively for the presence of DVST. Nonvisualization of the dural venous sinuses on 3D PC-MRV and signal changes supporting acute or subacute thrombus on T2- and T1-weighted images were considered a direct sign of DVST. Also, using circle region of interest (ROI) techniques, attenuation measurement from each sinus was obtained on NCCT. Sensitivity and specificity were computed for these modalities separately and in combination for diagnosis of DVST using digital subtraction angiography as the reference standard. RESULTS: Nonvisualization of venous sinuses on 3D PC-MRV (sensitivity 100%, specificity 71%) in combination with both applying Hounsfield unit (HU) threshold values of greater than 60 on NCCT (sensitivity 70%, specificity 94%) and acquiring signal changes supporting DVST on T2- and T1-weighted images (sensitivity 83%, specificity 96%), were found to have 100% sensitivity and 100% specificity in the identification of acute or subacute DVST. CONCLUSION: The combination of NCCT, T1- and T2-weighted MRI and 3D PC-MRV may allow the diagnosis of acute or subacute DVST and may obviate the need for contrast usage in patients with renal impairment or contrast allergies.